Dynamic nanoindentation testing: is there an influence on a material's hardness?. Issue 7 (3rd November 2017) - Leitner, A.; Maier-Kiener, V.; Kiener, D.
ABSTRACT: Modern nanoindentation devices are capable of dynamic experimentations, which allow us to exploit instrumented hardness tests extensively. Beside the assets of recording mechanical properties continuously over displacement, there are ongoing debates whether the superimposed force alters the material's hardness. We will show for a broad range of materials that significant hardness differences are noted between dynamic and static tests, even for large displacements. Those mainly result from a changing indentation strain-rate during the hold segment at peak load. This fact must be implicitly considered in studies using static indentation tests to guarantee comparability of obtained nanoindentation hardness values and derived quantities. GRAPHICAL ABSTRACT: IMPACT STATEMENT A mismatch between static and dynamic nanoindentation hardness has been identified to result from strain-rate deviations during hold segments in static nanoindentation tests, in particular affecting rate-sensitive materials.